A PRECARIZAÇÃO DO TRABALHO: DA REVOLUÇÃO INDUSTRIAL AO NEOLIBERALISMO - Aline Linares de Oliveira Scandelai (Universidade do Oeste Paulista, 2010)
This article is based on three decades of bibliographies and Web sites with content from reliable sources, which has aimed to outline the historical evolution of world of work, with emphasis on insecurity, wear and the different configurations of modes of production along the last two centuries. It highlights the emergence of the bourgeoisie as the class pioneer in the realization of the capitalist system and, taking as a starting point and landmark the Industrial Revolution, which has the fullness of the transformations in the relations between employer and employee and the manifestation of the social question in Europe in the mid nineteenth century to the twentieth century in Brazil.